PROLIPOSOMES: A BRIEF OVERVIEW OF NOVEL DELIVERY SYSTEM - JESSY SHAJI; VINAY BHATIA (International Journal of Pharma and Bio Sciences, 2013)
Liposomes are the most promising and broadly applicable of all the novel delivery systems. The poor stability associated with this system limits its long term storage. To overcome this issue Proliposomes were discovered by Payne et al. in 1986. Proliposomes are dry, free-flowing granular products composed of drug and phospholipid which, upon addition of water, disperse to form a multi-lamellar liposomal suspension. This paper reviews the method of preparation and evaluation of Proliposomes and highlights its potential to be exploited for different routes of administration.